Answer:
see explanation
Explanation:
Differentiate
using the quotient rule, given
y =
, then
=
![(g(x)f'(x)-f(x)g'(x))/(g(x)^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qoapdltjt1qllue774bp9sfzi2ozgmw983.png)
Here f(x) = 4 - x ⇒ f'(x) = - 1
g(x) = x ⇒ g'(x) = 1 , thus
=
=
= -
![(4)/(x^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zkmbnyt619vtxtmcyhvhysvmislvw36g1d.png)
-----------------------------------------
Given
y = 3x² +
, then
= 6x -
← evaluate for x = 2
= 6(2) -
= 12 - 1 = 11 ← as required
Let me know if you require assistance on (b) and (c)